Bio-inspired encapsulation and functionalization of iron oxide nanoparticles for biomedical applications. (5th January 2020) - Aisida, Samson O.; Akpa, Paul A.; Ahmad, Ishaq; Zhao, Ting-kai; Maaza, M.; Ezema, Fabian I.
Graphical abstract: Highlight: Bio-inspired encapsulation of Iron oxide nanoparticles for cancer therapy is presented. State-of-the-art synthetic routes and various surface architectures with biopolymers. Advances on, biocompatibility, and functionalization of FeNPs for drug delivery. Abstract: Cancer cells are typified by proliferating mass of cells that grow faster than other smaller cell tissues within the body. Efforts to combat this effect through chemotherapy, radiotherapy, immunotherapy and surgery are still challenging. Magnetic Iron oxide nanoparticles (FeO-NPs) encapsulated with biopolymers as a local drug delivery system with the control via an external magnetic field has been widely used as a drug delivery system in cancer therapy, minimizing the side effects and lack of pathological site-specific action common to the conventional approaches. For the FeO-NPs to function optimally in actualizing the applications as mentioned earlier, it requires that the FeO-NPs have high magnetization values, narrow particle size distribution and a special surface encapsulation. Biopolymers used for surface functionalization offer several advantages in biomedical applications, owing to their defined primary structures, nontoxicity, biocompatibility and biodegradability. The functionalized FeO-NPs offer various possibilities, which include targeting ligands, proteins, antibodies and covalent attachment of drugs using an external magnetic field for cancer therapeutic purposes. This work discusses recent advances in the development of FeO-NPs from fabrication to applications and the state-of-the-arts synthetic routes. The work gives special attention to the biopolymer surface functionalization of FeO-NPs now and future perspective of drug delivery in oncologic disease therapy chiefly cancer cells.